Cerebellar ataxia with neuropathy and vestibular areflexia syndrome (CANVAS). Issue 4 (August 2018) - Taki, Masakatsu; Nakamura, Takashi; Matsuura, Hiraku; Hasegawa, Tatsuhisa; Sakaguchi, Hirofumi; Morita, Kanako; Ishii, Ryotaro; Mizuta, Ikuko; Kasai, Takashi; Mizuno, Toshiki; Hirano, Shigeru
Abstract: Cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome (CANVAS) is a novel ataxic disorder consisting of the triad of cerebellar impairment, bilateral vestibular hypofunction, and a somatosensory deficit. We report the first Japanese case of CANVAS. The patient is a 68-year-old Japanese male. He was referred to our university for further evaluation of progressive gait disturbance and ataxia. He exhibited horizontal gaze-evoked nystagmus and sensory deficit. Nerve conduction studies showed sensory neuronopathy. Magnetic resonance imaging showed the atrophy of vermis but not of the brainstem. The caloric stimulation and video head impulse test (vHIT) showed bilateral vestibulopathy. The visually enhanced vestibulo-ocular reflex (VVOR) was also impaired. In addition to neurological and electrophysiological examinations, simple neuro-otological examinations (i.e., caloric stimulation, vHIT, and VVOR) may reveal more non-Caucasian cases.